2018
DOI: 10.1111/ijlh.12846
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of rivaroxaban concentrations demonstrates lack of clinical utility of a PT, dPT and APTT test in estimating levels

Abstract: The PT and aPTT show poor correlation with rivaroxaban levels measured by calibrated anti-Xa and HPLC-MS/MS assays. A normal combined PT and APTT identified low rivaroxaban levels with high specificity but lacked sensitivity. The dPT assay at several dilutions could not be used to quantify rivaroxaban in clinical samples. The utility of these PT, aPTT and dilute PT assays in a clinical setting is very limited, and results generated must be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Baglin et al (9) presented three main methodologies for rivaroxaban monitoring: activated partial thromboplastin time (APTT), prothrombin time (PT), and determination of plasma drug levels or drug concentration. Although they are easily available and cheap, APTT and PT assays are not ideal assays for rivaroxaban measurement due to a discreet variation compared to normal values and a high dependency on the reagent used (10 13). As Thom et al (13) reported, these tests present high specificity but lack sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baglin et al (9) presented three main methodologies for rivaroxaban monitoring: activated partial thromboplastin time (APTT), prothrombin time (PT), and determination of plasma drug levels or drug concentration. Although they are easily available and cheap, APTT and PT assays are not ideal assays for rivaroxaban measurement due to a discreet variation compared to normal values and a high dependency on the reagent used (10 13). As Thom et al (13) reported, these tests present high specificity but lack sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are easily available and cheap, APTT and PT assays are not ideal assays for rivaroxaban measurement due to a discreet variation compared to normal values and a high dependency on the reagent used (10 13). As Thom et al (13) reported, these tests present high specificity but lack sensitivity. In another work, our group also demonstrated this characteristic (14).…”
Section: Introductionmentioning
confidence: 99%
“…Further work is needed to understand these issue more comprehensively in dogs. An alternative approach described in people is the use of dilute PT (dPT), which may create a more physiological in vitro environment compared to standard PT 26–28 . There are conflicting reports, however, regarding the suitability of dPT assays as a surrogate for RIVA in people 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach described in people is the use of dilute PT (dPT), which may create a more physiological in vitro environment compared to standard PT 26–28 . There are conflicting reports, however, regarding the suitability of dPT assays as a surrogate for RIVA in people 26,27 . Dilute PT has been investigated in healthy cats receiving rivaroxaban 29 but to the authors’ knowledge has not been examined in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…The search strategy identified 9169 citations. After reviewing titles and abstracts, 16 articles [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] evaluating the performance of coagulation indices were included in the systematic review. Among them, five studies in total were included in the quantitive analysis for rivaroxaban and dabigatran [11][12][13][14]23].…”
Section: Study Identification and Selectionmentioning
confidence: 99%